DESIGN AND ANALYSIS OF LOAD CHARACTERISTICSWITH A LARGE DIMENSION CONIC ULTRASONIC HORN - ZHANG NingNing; GENG SenLin (Jixie qiangdu)
The inherent frequency of longitudinal vibration of a large section of conical horn was deduced by Rayleigh’ s approximate theoretical hypotheses,and the frequency of expression of correction is obtained. Effect of load on a large section of conical horn amplification coefficient and resonant frequency was studied. Modal analysis and the load characteristics of a set of large conic dimension transformers were analyzed by the finite element analysis. The results show that corrected result is closer to the value of the finite element simulation Compared with the one-dimensional theory and Its applicable scope is bigger. Along with the load increasing diameter and length of the system frequency will decrease gradually,and the amplification coefficient will increase Constantly and the effects of the diameter of a length is more significant relatively. The results provide a theoretical basis for design of conical horn section of engineering calculation and the compound horn and practical application.